2018
DOI: 10.1021/acsanm.8b00968
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Stratification in Binary Colloidal Films from Microbeam X-ray Scattering: Toward Optimizing the Evaporative Assembly Processes for Coatings

Abstract: Colloidal films have many important applications where a layered configuration is desirable, including flexible electronics, anti-reflective coatings, and anti-microbial paints. We report stratification during evaporative film formation in binary colloidal dispersion, probed using a novel microbeam small-angle X-ray scattering (SAXS) technique. To our knowledge, SAXS approaches have not been used to experimentally obtain quantitative data of concentration profiles in multicomponent colloidal films. We measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…However, experimental data shows that this does not occur, and the surface is made up predominantly of large latex particles. These results are similar to those obtained by Carr et al which suggest that the ZJD model overpredicts small-on-top stratification 51,52 .…”
Section: Resultssupporting
confidence: 91%
“…However, experimental data shows that this does not occur, and the surface is made up predominantly of large latex particles. These results are similar to those obtained by Carr et al which suggest that the ZJD model overpredicts small-on-top stratification 51,52 .…”
Section: Resultssupporting
confidence: 91%
“…Previous studies demonstrated that self-stratification will only happen for polymers of specific chemistry or particle mixtures of certain size ratios when a coating suspension dries. [13][14][15][16][17][18] These constraints severely limit the application of self-stratification in common coating materials. In order to achieve effective stratification, current coating formulation and binder chemistry need to be comprehensively altered, which demands significant efforts.…”
Section: Introductionmentioning
confidence: 99%
“…This signifies that the film formation process involving particle migration is an intricate process, controlled by several factors including the particle dimensions, interactions, solvent system, processing parameters and others. 28 Most of these studies focused on binary mixtures of latex dispersions with film forming temperature above room temperature which enabled to retain their original particle dimensions during the film forming process. In real scenario, most latex systems have a film forming temperature below room temperature to enable film formation without application of external heat.…”
Section: Introductionmentioning
confidence: 99%